Driving risk and spend out of the global supply chain - Cook, Thomas A. 1953- (The global warrior series, 2015)
The book examines all the areas where spend can be reduced and details a specific strategy to help readers reduce spend without compromising values. Providing the most comprehensive and up-to-date compilation of material and tactics currently available for international business professionals, the text supplies a clear understanding of the steps readers must take before taking any action to reduce risk and spend in their import, export, and domestic supply chain operations